Immunotherapy Based on Dendritic Cell-Targeted/-Derived Extracellular Vesicles—A Novel Strategy for Enhancement of the Anti-tumor Immune Response - Markov, Oleg; Oshchepkova, Anastasiya; Mironova, Nadezhda (Frontiers in Pharmacology, 2019)
Dendritic cell (DC)-based anti-tumour vaccines have great potential for the treatment of cancer. To date, a large number of clinical trials involving DC-based vaccines have been conducted with a view to treating tumours of different histological origins. However, DC-based vaccines had several drawbacks including problems with targeted delivery of tumour antigens to DCs and prolong storage of cellular vaccines. Therefore, the development of other immunotherapeutic approaches capable of enhancing the immunogenicity of existing DC-based vaccines or directly triggering anti-tumour immune responses is of great interest. Extracellular vesicles (EVs) are released by almost all types of eukaryotic cells for paracrine signaling. EVs can interact with target cells and change their functional activity by delivering different signaling molecules including mRNA, non-coding RNA, proteins, and lipids. EVs have potential benefits as natural vectors for the delivery of RNA and other therapeutic molecules targeted to DCs, T-lymphocytes, and tumour cells; therefore, EVs are a promising entity for the development of novel cell-free anti-tumour vaccines that may be a favourable alternative to DC-based vaccines. In the present review, we discuss the anti-tumour potential of EVs derived from DCs, tumours, and other cells. Methods of EV isolation are systematised, and key molecules carried by EVs that are necessary for the activation of a DC-mediated anti-tumour immune response are analysed with a focus on the RNA component of EVs. Characteristics of anti-tumour immune responses induced by EVs in vitro and in vivo are reviewed. Finally, perspectives and challenges with the use of EVs for the development of anti-tumour cell-free vaccines are considered.